Epidemiology of myasthenia gravis in Northern Portugal: Frequency estimates and clinical epidemiological distribution of cases. Issue 3 (4th July 2016) - Santos, Ernestina; Coutinho, Ester; Moreira, Isabel; Silva, Ana Martins; Lopes, Dina; Costa, Henrique; Silveira, Fernando; Nadais, Goreti; Morais, Hugo; Martins, João; Branco, Maria Ceu; Veiga, Andreia; et al.
ABSTRACT: Introduction : In this study we estimated the prevalence, incidence, and mortality of myasthenia gravis (MG) in northern Portugal and characterized the clinical features of the patients identified. Methods : We used 2 data sources: clinical records from the hospitals and pyridostigmine prescription registers. Results : On December 31, 2013, we estimated a point prevalence of 111.7 patients per million population. The highest prevalence was observed in the group >65 years of age, especially in men (288.1 per million). During 2013, we estimated an incidence rate of 6.3 per million per year. Among women, the incidence rate was highest in the 15–49‐year age group; in men, incidence increased with age up to 22.1 per million in those >65 years old. The MG‐related mortality rate was 0.5 per million. Conclusions : These figures are in keeping with similar studies and emphasize the importance of diagnosis and management of MG in elderly populations. Muscle Nerve 54 : 413–421, 2016